Review on comprehending and enhancing the initial Coulombic efficiency of anode materials in lithium-ion/sodium-ion batteries. (November 2020) - Li, Xin; Sun, Xiaohong; Hu, Xudong; Fan, Fengru; Cai, Shu; Zheng, Chunming; Stucky, Galen D.
Abstract: Developing lithium-ion batteries (LIBs)/sodium-ion batteries (SIBs) with high energy density is vital to meet increasingly demanding requirements for energy storage. The initial Coulombic efficiency (ICE) of LIBs and SIBs anode materials, which is associated with the amount of redundant cathode materials in full cells, is a key parameter for the improvement of energy density in batteries. Generally, the low ICE of anode materials is compensated by additional loading of cathode materials in current commercial LIBs. Nevertheless, because the specific capacity of common lithium-metal oxide cathodes is lower than that of anodes, an excessive amount of cathode materials (10%–15% for graphite anode material) must be added to overcome the insufficient ICE of anode materials, which leads to an appreciable reduction of energy density. Specifically, the reduction is about 5%–20% of total available capacity in commercial graphite electrodes; and, it can even be as high as 15–50% for next-generation high-capacity anode materials (such as Si and Sn). Much work has been devoted to exploring anode materials with high ICE in LIBs/SIBs; however, to the best of our knowledge, there does not yet exist a comprehensive review. Herein, we provide an overview of ICE of anode materials both in LIBs and SIBs. In this review, we first discuss the current understanding of the association between ICE and energy density. This is followed by a detailed assessment of the reasons of the initial capacity loss (low ICE) for various types of anode materials. A summary is then given of the growing number of methods and related fundamental mechanisms being used to enhance ICE. We conclude with a perspective on the current challenges and promising research directions that might lead to further improvements of the ICE and the fabrication of higher-energy-density batteries. Graphical abstract: Image 1 Highlights: Relationship between initial Coulombic efficiency and energy density. Causes of low initial Coulombic efficiency. Methods and related mechanisms to improve initial Coulombic efficiency.